The Influence of Leadership and Workload to Employee Performance With Work Environment as Mediating Variable in Medium Customs and Excise Office of Ambon - Atihuta, Agustu (Jurnal Pendidikan Tambusai, 2021)
The purpose of this study is to analyze leadership and workload that affects the performance of employees in Medium Customs and Excise Office of Ambon with work environment as mediating variable. The methodology used in this study uses quantitative methods. The population in this study is all employees and leaders at the all levels at the Medium Customs and Excise Office of Ambon. The respondents involved in this study were 55 employees of Medium Customs and Excise Office of Ambon. The questionnaire used for the study is likert scale method. The results of the questionnaire were processed using PLS-SEM. The results of this study indicate that leadership has significant effect to employee performance and minor effect with work environment as mediating variable. However, workload has negative effect to employee performance but work environment provide opposite effect to employee performance. Work environment serves positive outcomes to employee performance.